2015
DOI: 10.1002/cne.23821
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AⅡ amacrine, displaced amacrine, and bistratified ganglion cell types in human retina with antibodies against calretinin

Abstract: Antibodies against calretinin are markers for one type of rod pathway interneuron (AⅡ amacrine cell) in the retina of some but not all mammalian species. The AⅡ cells play a crucial role in night-time (scotopic) vision and have been proposed as a target for optogenetic restoration of vision in retinal disease. In the present study we aimed to characterize the AⅡ cells in human retina. Postmortem human donor eyes were obtained with ethical approval and processed for calretinin immunofluorescence. Calretinin-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 73 publications
3
47
0
Order By: Relevance
“…CaR has been demonstrated to specifically label AII ACs in most mammalian species (rabbit – Völgyi et al, 1997; Massey and Mills, 1999; monkey – Mills and Massey, 1999; cat – Goebel and Pourcho, 1997; human – Kántor et al, 2016b; Lee et al, 2016), whereas starburst but not AII ACs express CaR in the rat and the mouse retina (Gábriel and Witkovsky, 1998; Haverkamp and Wässle, 2000). These observations were confirmed here showing that AII ACs in the rabbit, cat, and monkey retina express CaR, whereas AII ACs in the rat and the mouse did not.…”
Section: Discussionmentioning
confidence: 99%
“…CaR has been demonstrated to specifically label AII ACs in most mammalian species (rabbit – Völgyi et al, 1997; Massey and Mills, 1999; monkey – Mills and Massey, 1999; cat – Goebel and Pourcho, 1997; human – Kántor et al, 2016b; Lee et al, 2016), whereas starburst but not AII ACs express CaR in the rat and the mouse retina (Gábriel and Witkovsky, 1998; Haverkamp and Wässle, 2000). These observations were confirmed here showing that AII ACs in the rabbit, cat, and monkey retina express CaR, whereas AII ACs in the rat and the mouse did not.…”
Section: Discussionmentioning
confidence: 99%
“…GABA-immunoreactive amacrine cells are characterized by medium and wide-field processes, and several wide-field types contain a second neuroactive substance, including vasoactive intestinal polypeptide, substance P, acetylcholine, or dopamine (Brecha et al, 1988; Wässle and Chun, 1988; Vaney et al, 1989; Casini and Brecha, 1992; Strettoi and Masland, 1996; Akrouh and Kerschensteiner, 2015; Park et al, 2015). In contrast, the glycine-immunoreactive amacrine cells have narrow-field processes that span multiple IPL laminae, and several types also contain a second immunohistochemical marker, including parvalbumin, calretinin and Disabled 1 (Wässle et al, 1993; Haverkamp and Wässle, 2000, 2004; Rice and Curran, 2000; Lee et al, 2006, 2016). An exception to this general principle is that VGluT3-immunoreactive amacrine cells, which have medium-field processes distributed to multiple IPL laminae, exhibit both glycine and glutamate immunoreactivity (Haverkamp and Wässle, 2004; Johnson et al, 2004; Grimes et al, 2011; Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach identifying AII amacrine cells is using immunohistochemistry with antibodies to parvalbumin in rabbit (Casini et al, 1995) and rat (Wässle et al, 1993), while antibodies to calretinin have been used in cat (Pasteels et al, 1990; Gábriel and Straznicky, 1992; Macneil et al, 2009), macaque (Wässle et al, 1995; Massey and Mills, 1999; Kolb et al, 2002), rabbit (Massey and Mills, 1999) and human (Lee et al, 2004, 2016). Lastly, disabled 1 has been used in mouse (Rice and Curran, 2000; Lee et al, 2004, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In primate retina, the expression of calcium binding proteins shows common pattern as well as species specific differences (Chiquet, Dkhissi‐Benyahya, & Cooper, ; Pasteels, Rogers, Blachier, & Pochet, ). For example, in all primate retinas studied to date, calretinin is expressed in AII amacrine cells (macaque: Kolb, Zhang, Dekorver, & Cuenca, ; Mills & Massey, ; Wässle, Grünert, Chun, & Boycott, , marmoset: Jusuf, Lee, & Grünert, ; Weltzien, Percival, Martin, & Grünert, , and human: Lee, Weltzien, Madigan, Martin, & Grünert, ). The expression of calretinin in the ganglion cell layer, however, varies between primate species.…”
Section: Introductionmentioning
confidence: 99%
“…In macaque retina, calretinin expression in the ganglion cell layer is downregulated after birth (Hendrickson, Yan, Erickson, Possin, & Pow, ), thus these cells are rare in the adult. In human retina, the majority of calretinin expressing cells in the ganglion cell layer are displaced amacrine cells, and calretinin expressing ganglion cells have been identified as bistratified cells (Lee et al, ). In marmoset, calretinin expressing cells make up a clear subpopulation of cells in the ganglion cell layer (Chiquet et al, ; Jusuf et al, ) but the cell types have not been identified.…”
Section: Introductionmentioning
confidence: 99%